Cell-Free DNA: Hope and Potential Application in Cancer - Yan, Yan-yan; Guo, Qiao-ru; Wang, Feng-hua; Adhikari, Rameshwar; Zhu, Zhuang-yan; Zhang, Hai-yan; Zhou, Wen-min; Yu, Hua; Li, Jing-quan; Zhang, Jian-ye (Frontiers in Cell and Developmental Biology, 2021)
Cell-free DNA (cfDNA) could serve as a novel and easily accessible biomarker in many cancers. A broad range of cfDNA applications are currently being investigated by multiple international research groups and companies, touching different stages of cancer management. In this review, we will discuss the potential clinical relevance of cfDNA in oncology: cancer diagnosis and early screening; cancer therapeutic effect evaluation and monitoring disease progression; and prognosis determination.